2016
DOI: 10.1039/c5sm02604k
|View full text |Cite
|
Sign up to set email alerts
|

Open boundary molecular dynamics of sheared star-polymer melts

Abstract: Open boundary molecular dynamics (OBMD) simulations of a sheared star polymer melt under isothermal conditions are performed to study the rheology and molecular structure of the melt under a fixed normal load. Comparison is made with the standard molecular dynamics (MD) in periodic (closed) boxes at a fixed shear rate (using the SLLOD dynamics). The OBMD system exchanges mass and momentum with adjacent reservoirs (buffers) where the external pressure tensor is imposed. Insertion of molecules in the buffers is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 102 publications
(238 reference statements)
2
58
0
Order By: Relevance
“…Current efforts are also focusing on combining AdResS and advance sampling techniques, e.g., metadynamics 63 . Another direction of AdResS development is considering simulations of open grand-canonical systems 64 , e.g., the grand-canonical (GC)-AdResS 65, 66 and open boundary molecular dynamics (OBMD) approaches 67, 68 . To properly model the hexagonal to orthorhombic phase transition all of these techniques would need to be combined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current efforts are also focusing on combining AdResS and advance sampling techniques, e.g., metadynamics 63 . Another direction of AdResS development is considering simulations of open grand-canonical systems 64 , e.g., the grand-canonical (GC)-AdResS 65, 66 and open boundary molecular dynamics (OBMD) approaches 67, 68 . To properly model the hexagonal to orthorhombic phase transition all of these techniques would need to be combined.…”
Section: Methodsmentioning
confidence: 99%
“…The whole DNA array is at all times modeled at full atomistic resolution, but since the region outside the semipermeable walls is used only as a solution reservoir, it can be modeled with the coarse-grained resolution, acting in a similar way as a buffer in an OBMD simulation 67, 68 . We perform our multiscale simulations, with a length of 22 ns (2 ns equilibration followed by 20 ns production runs) for each system or 900 ns of production runs in total, employing AdResS.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently completed a series of works on star polymer dynamics 19,26,27 . This series started by a study of the effect of open boundaries compared with closed systems in the rheology of melts under shear (simulations using Open Boundary Molecular Dynamics (OBMD) [26][27][28] permits to fix the pressure load and shear stress, instead of the density and shear velocity). As a continuation of such work, we studied the dynamics of stars in solution and melt 19 and observed that the tank-treading frequency of monomers around the molecule's CoM, ω R , was completely different from the "apparent" angular velocity obtained from the standard (lab-frame) analysis ω.…”
Section: Introductionmentioning
confidence: 99%
“…To perform a truly open grand-canonical molecular simulations one should take recourse to the open boundary molecular dynamics (OBMD) [57,116,[136][137][138] that permits simulations directly in the grand-canonical ensemble. The OBMD method combines features of AdResS and open MD [139,140], which enable the exchange of energy, momentum, and matter with the external environment through the imposed arbitrary time-dependent external pressure tensor.…”
Section: Discussionmentioning
confidence: 99%